ANALISIS FAKTOR RESIKO TERHADAP SANITASI KAPAL DI PELABUHAN BATU AMPAR - Chandra Putra; Zulkarnain Zulkarnain; Musrifin Ghalib (Program Pascasarjana Universitas Riau, 2018)
Background and Objectives : Sanitation is an effort to prevent disease by eliminating or controlling environmental risk factors which are the chain of disease transmission. This study aims to analyze the ship sanitation component based on the regulation of the minister of health and add two other components, namely the knowledge of the crew and the role of port health workers. Material and Method : Ships are water vehicles of any type and type that are driven by mechanical power, wind power or delayed including dynamic supporting vehicles. The analysis used in this study is inferential statistical analysis namely ANOVA to see the role of two other indicators (knowledge of X4 crew and the role of health workers X5) in addition to 14 indicators according to the minister of health regulations consisting of Food Sanitation (X1), Water Sanitation (X2 ), Waste Management (X3), Shipbuilding Knowledge (X4), Role of Health Workers (X5). Results : Statistically using ANOVA as a whole there is a significant effect on Ship Sanitation, but after further testing after ANOVA there were several pair of indicators that did not significantly influence the pair X14 and X45. As we know that, the instrument used in the scientific study of this study is a questionnaire that was built from indicators on the checklist of vessel sanitation hygiene checks. If further analysis shows that the ABK knowledge indicator (X4) that has existed so far is often overlooked because there is almost no supporting facility in providing short training (courses) to ship crews in improving competence in the shipping sector. Conclusion : Based on post ANOVA analysis of five indicators, ABK knowledge indicators are very insignificant because of the very lack of facilities or those responsible for accommodating ship crews to improve competence, so that their understanding of ship sanitation which is a prerequisite for obtaining yacht permits has no role important as issued by the regulation of the health minister of the Republic of Indonesia.